Three new species of Collembola (Arthropoda: Hexapoda) from Central Brazilian shallow caves: side effects of long term application of environmental law on conservation - Zeppelini, Douglas; Brito, Roniere A.; Lima, Estevam C. A. (Zootaxa, 2018)
Three new species of Collembola are described from small shallow caves in Southeastern Brazil: Arrhopalites glabrofasciatus sp. nov., Pseudosinella ambigua sp. nov. and Pseudosinella guanhaensis sp. nov. The species were found in surveys performed as part of the process to accomplish the permits for high impact enterprising. The change in the legislation is discussed and a suggestion is made to improve the process. The long term effects of the law resulted in the discovery of many new species and genera, most of them being (or to be) described.